Resident Sleep During Traditional Home Call Compared to Night Float - Apoorva Chowdhary; John A. Davis; Leona Ding; Parisa Taravati; Shu Feng (Journal of Academic Ophthalmology, 2023)
Purpose This article aims to compare resident sleep while on night float with a traditional home call.